Hubungan Game Online Dengan Pola Makan, Aktivitas Fisik Dan Status Gizi Remaja - Rachman, Riska Novia; Ratnasari, Diah; Duvita, Anggray (Pontianak Nutrition Journal (PNJ), 2025)
One of them is popular among school children. Addiction to online gaming, which causes several negative impacts on children such as disturbed children’s diet and also rarely do activities because online gaming is usually done by sitting and even lying down. The purpose of this study wa to analyze the relationship of online game addiction with diet, physical activity and nutritional status of adolescents. The method used in this study uses descriptive correlation research. The design used is with a Cross Sectional approach. The sample in this study were 56 students who met the criteria. Spearman Correlation the results of game addiction variables with energy intake are p<0,05 (p=0,016), online game addiction variables with physical activity (p=0,001), online game adiction variables with nutritional status (p=0,005). The conclusion of this study is that there is a relationship between online game addiction with diet, physical activity an nutritional status in adolescents at MTS Assalafiyah tegal city.